2021
DOI: 10.4067/s0718-221x2021000100426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microcrystalline cellulose on some performance properties of chitosan aerogels

Abstract: The aim of this research was to investigate the effect of the microcrystalline cellulose reinforcement on some physical, mechanical, thermal, and morphological properties of the chitosan aerogels. The bio-based chitosan aerogels were produced using chitosan as a matrix and the microcrystalline cellulose as a reinforce material through the freeze-drying method. The aerogel suspensions were prepared in five different ratios to investigate the effect of microcrystalline cellulose content. The density, porosity, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…It was found that the use of boric acid to dissolve chitosan improved the thermal stability of the samples. While the mass loss of the A-0 coded sample was 54.6% in the present study, Ozen et al (2021) reported the mass loss of chitosan foams reinforced with microcrystalline cellulose, prepared by dissolving in acidic acid, were changed between 74.6% and 85.6%. The main reason for superior thermal properties is that the boric acid prevented the diffusion of oxygen and heat so that the combustion could be effectively retarded during pyrolysis (Yu et al 2017).…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…It was found that the use of boric acid to dissolve chitosan improved the thermal stability of the samples. While the mass loss of the A-0 coded sample was 54.6% in the present study, Ozen et al (2021) reported the mass loss of chitosan foams reinforced with microcrystalline cellulose, prepared by dissolving in acidic acid, were changed between 74.6% and 85.6%. The main reason for superior thermal properties is that the boric acid prevented the diffusion of oxygen and heat so that the combustion could be effectively retarded during pyrolysis (Yu et al 2017).…”
Section: Resultscontrasting
confidence: 55%
“…There have been many studies about chitosan and cellulose-based or reinforced foams. Compression modulus of chitosan and cellulose-based foams that had different densities were determined to range from 10 to 1300 KPa (Wang et al 2017;Michailidou et al 2019;Ozen et al 2021) and 15 to 2800 KPa (Gibson and Ashby 1997;Liu et al 2017), respectively. In contrast, activated carbon-reinforced foam has been evaluated in few studies and could not notably enhance the mechanical properties of foams (Ketkul et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…(2020) stated that the porosity value of the materials produced for porous tissue scaffolds from deoxyribonucleic acid sodium salt and chitosan varies between 49% and 62% 75 . Chitosan-based aerogels reinforced with microcrystalline cellulose and their density and porosity values ranged 0.03 g/cm 3 to 0.11 g/cm 3 and 94.73% to 62.30%, respectively 19 . As a result, the density and porosity values of the PVAc foams in this study were found to be compatible with the literature.…”
Section: Density and Porosity Determinationmentioning
confidence: 99%
“…Disposal of waste is significantly excluded on a global scale due to increasing environmental awareness. Therefore, researchers were focused on environmentally compatible reinforcement materials in recent years [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric materials are lighter, easier to process, and have lower production costs in comparison to other materials. 1,2 In addition, polymers can be classified as thermosets and thermoplastics depending on their formability. 3 Elastomers are similar to thermosets since they cannot be reshaped once they take shape.…”
Section: Introductionmentioning
confidence: 99%